2003
DOI: 10.1519/1533-4287(2003)017<0374:awtsei>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Adding Weights to Stretching Exercise Increases Passive Range of Motion for Healthy Elderly

Abstract: Stretching exercise is effective for increasing joint range of motion (ROM). However, the Surgeon General's Report and the American College of Sports Medicine cite a lack of studies identifying strategies capable of increasing the effectiveness of stretching exercise. This investigation evaluated adding modest weight (0.45-1.35 kg) to a stretching exercise routine (Body Recall [BR]) on joint ROM. Forty-three subjects ages 55-83 years participated in 1 of 2 training groups, BR, BR with weights (BR+W), or a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 0 publications
2
27
0
5
Order By: Relevance
“…An average score of 12 out of 18 was assessed for the experimental single-group studies ( n = 3). Fourteen articles were conducted in the United States [10–12, 14, 15, 17, 18, 20, 22, 25–29], while the remainder of the studies were from Japan [19], Brazil [23, 24], Turkey [21], Australia [9, 16], Taiwan [30], and Canada [13]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An average score of 12 out of 18 was assessed for the experimental single-group studies ( n = 3). Fourteen articles were conducted in the United States [10–12, 14, 15, 17, 18, 20, 22, 25–29], while the remainder of the studies were from Japan [19], Brazil [23, 24], Turkey [21], Australia [9, 16], Taiwan [30], and Canada [13]. …”
Section: Resultsmentioning
confidence: 99%
“…One study also used brain imaging for the purposes of identifying changes in hippocampal volume with training [20]. A common outcome measure was simply whether there was a change in range of motion usually assessed by goniometry [15, 17, 20, 2428, 30]. The inclusion of these studies in the review (although they reported no “functional outcome”) was to provide the data for the purpose of determining whether older adults would, in fact, improve range of motion about different joints with various flexibility exercise programs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicated that elastic band exercises improved maximal voluntary thigh muscle strength (Binder et al, 2005); increased isometric, isotonic, and isokinetic muscle strength (Ribeiro et al, 2009;Webber & Porter, 2010;Woo, Hong, Lau, & Lynn, 2007); improved muscle strength and flexibility (Latham & Liu, 2010;Nelson et al, 2007); promoted muscle hypertrophy (Yasuda et al, 2014); improved movement time (Webber & Porter, 2010); improved knee extension and hip extension strength (Dancewicz, Krebs, & McGibbon, 2003); and sit-to-stand performance of older adults (Chen et al, 2009b). Furthermore, elastic band resistance training improved functional ability (Topp, Boardley, Morgan, Fahlman, & McNevin, 2005), increased flexibility and range of joint motion (Sugimoto & Blanpied, 2006;Swank, Funk, Durham, & Roberts, 2003), and enhanced gait and balance of older adults (Topp, Mikesky, Dayhoff, & Holt, 1996).…”
Section: Introductionmentioning
confidence: 99%